Roles of benthic foraminifera in carbon cycling at marginal oceans with active tectonic forcing: in situ experiment and observations - Kitazato, Hiroshi; Oguri, Kazumasa; Glud, Ronnie N.; Nomaki, Hidetaka (Anuário do Instituto de Geociências, 2006)
Abstract